Soccer and Regional Development. An Analysis of the Regional Economic Impacts of a Bundesliga Soccer Club—Using the Example of Borussia VfL 1900 Mönchengladbach - Hamm, Rüdiger; Jäger, Angelika; Fischer, Christina (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Soccer—the world’s most important triviality—is not only the most popular sport in Europe, but has furthermore become an increasingly important research subject for various scientific disciplines. For regional economists and policy advisers, especially the estimation of regional economic impacts of soccer clubs and their regular major sport events are of high importance and interest. Whereas athletic success and challenges are achieved within the stadium, along with the popularity of the soccer club and its athletes, significant economic benefits can arise for the cities and regions hosting a soccer club. The purpose of this article is to analyze and estimate the impact, the German national league soccer club Borussia VfL 1900 Mönchengladbach exerts on its surrounding region, the Middle Lower Rhine Region in North Rhine-Westphalia, Germany. The analysis differentiates expenditure-based and supply side effects. On one hand, the value added effect for the hosting region is estimated at nearly 100 mio. € annually. In addition, employment effects arise from the 1.075 employees working for the club. On the other hand, the results indicate that the club’s effects on the region’s perception, awareness and public image—which are mostly not included in comparable scientific studies, as it is difficult to quantify and measure these effects—are significant and should no longer be neglected in cost-benefit analysis of large sporting events. The results also suggest the existence of a positive influence on the local identity and sense of belonging of the population that is characterized in this study as “psychological income”. Summarized, a soccer club is identified as a significant and valuable location factor.